2014
DOI: 10.1186/cc13905
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of peripheral perfusion to predict postoperative complications after major abdominal surgery early: a prospective observational study in adults

Abstract: IntroductionAltered peripheral perfusion is strongly associated with poor outcome in critically ill patients. We wanted to determine whether repeated assessments of peripheral perfusion during the days following surgery could help to early identify patients that are more likely to develop postoperative complications.MethodsHaemodynamic measurements and peripheral perfusion parameters were collected one day prior to surgery, directly after surgery (D0) and on the first (D1), second (D2) and third (D3) postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 50 publications
0
85
1
Order By: Relevance
“…Similarly, improvement of capillary refill and skin mottling over time appears to parallel a decrease in visceral organ and renal vascular tone, respectively. This observation could for the first time provide an explanation for the published evidence on a strong relationship between clinical parameters of peripheral perfusion, arterial lactate, base deficit, organ function, and mortality [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, improvement of capillary refill and skin mottling over time appears to parallel a decrease in visceral organ and renal vascular tone, respectively. This observation could for the first time provide an explanation for the published evidence on a strong relationship between clinical parameters of peripheral perfusion, arterial lactate, base deficit, organ function, and mortality [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 89%
“…Patients with abnormal peripheral perfusion, assessed by either skin temperature or color, had higher odds of hyperlactatemia and organ failure [7] and a high risk of death [8]. Even in postsurgery patients with a very low incidence of death, skin perfusion as assessed by the capillary refill time was related to increased morbidity [9]. In septic shock patients, Ait-Oufella et al [10] showed that the capillary refill time measured at 6 hours of resuscitation was related to lactate levels, organ dysfunction, and mortality.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies already showed that a CRT >5.0 s following initial haemodynamic optimization discriminated haemodynamically stable patients with more severe organ dysfunction and higher odds for worsening organ failure [20][21][22][23].…”
Section: Key Pointsmentioning
confidence: 99%
“…In 60 patients with septic shock, the mottling score 6 hours after the initial resuscitation was strongly associated with 14-day mortality, and patients with a higher 6-hour mottling score had increased mortality on days 1 and 2. 55 The CRT was also found to be reproducible, 56,57 although the thresholds indicative of altered perfusion vary between studies (ranging from 2.4 to 5 seconds). In 59 patients with septic shock, the index finger and knee CRTs were predictive of 14-day mortality (index finger threshold 2.4 seconds, area under curve [AUC] 84%; knee threshold 4.9 seconds, AUC 90%).…”
Section: Sepsis/septic Shockmentioning
confidence: 99%
“…Several recent studies provide examples of how to standardize and interpret the assessment for mottling [53][54][55] and CRT. 56,57 Using laser Doppler flow, Ait-Oufella et al 53,55 measured the microvascular flow on the lower extremity, and a standardized scoring system was created (Table 2). In 60 patients with septic shock, the mottling score 6 hours after the initial resuscitation was strongly associated with 14-day mortality, and patients with a higher 6-hour mottling score had increased mortality on days 1 and 2.…”
Section: Sepsis/septic Shockmentioning
confidence: 99%